The Hemoglobin Homolog Cytoglobin in Smooth Muscle Inhibits Apoptosis and Regulates Vascular Remodeling. Issue 10 (October 2017) - Jourd'heuil, Frances L.; Xu, Haiyan; Reilly, Timothy; McKellar, Keneta; El Alaoui, Chaymae; Steppich, Julia; Liu, Yong Feng; Zhao, Wen; Ginnan, Roman; Conti, David; Lopez-Soler, Reynold; Asif, Arif; et al.
Abstract : Objective—: The role of hemoglobin and myoglobin in the cardiovascular system is well established, yet other globins in this context are poorly characterized. Here, we examined the expression and function of cytoglobin (CYGB) during vascular injury. Approach and Results—: We characterized CYGB content in intact vessels and primary vascular smooth muscle (VSM) cells and used 2 different vascular injury models to examine the functional significance of CYGB in vivo. We found that CYGB was strongly expressed in medial arterial VSM and human veins. In vitro and in vivo studies indicated that CYGB was lost after VSM cell dedifferentiation. In the rat balloon angioplasty model, site-targeted delivery of adenovirus encoding shRNA specific for CYGB prevented its reexpression and decreased neointima formation. Similarly, 4 weeks after complete ligation of the left common carotid, Cygb knockout mice displayed little to no evidence of neointimal hyperplasia in contrast to their wild-type littermates. Mechanistic studies in the rat indicated that this was primarily associated with increased medial cell loss, terminal uridine nick-end labeling staining, and caspase-3 activation, all indicative of prolonged apoptosis. In vitro, CYGB could be reexpressed after VSM stimulation with cytokines and hypoxia and loss of CYGB sensitized human and rat aortic VSM cells to apoptosis. This was reversed after antioxidant treatment or NOS2 (nitric oxide synthase 2) inhibition. Conclusions—: These results indicate that CYGB is expressed in vessels primarily in differentiated medial VSM cells where it regulates neointima formation and inhibits apoptosis after injury. Abstract : Supplemental Digital Content is available in the text.